МІКРОМЕРЕЖІ: СУЧАСНИЙ СТАН І ПЕРСПЕКТИВИ РОЗВИТКУ - Кучерява, І.М. (Інститут електродинаміки Національної академії наук України, 2025)
This paper presents a review of the microgrid concept, classification, basic advantages, principles of the design and operation, electricity generation resources, battery energy storage, microgrid control systems. The up-to-date industrial microgrids are characterized, their actual tasks are given. The perspective issues and important aspects of future microgrid studies are explained. References 54, figures 10, tables 7.